Designing Pro-Poor Water and Sewer Concessions : Early Lessons from Bolivia - Komives, Kristin (The World Bank, 1999)
To design pro-poor concession arrangements in the water sector, policymakers must pay careful attention to how the proposed contract, and existing or proposed regulations, will affect private concessionaires' ability, obligations, and financial incentives to serve low-income households. - The Bolivian government awarded a concession for water and sewer services in La Paz and El Alto in 1997. One goal of doing so was to expand in-house water and sewer service to low-income households. Komives uses the Aguas del Illimani case to explore how the design of typical concession agreements (with monopoly private service suppliers) can affect outcomes in poor neighborhoods. She finds that outcomes in services can be affected by the concession contracts, by the contract bid process, by sector regulations, and by regulatory arrangements. To increase the likelihood of improvements in low-income areas, policymakers should: · Make contract objectives clear and easily measurable. · Eliminate policy barriers to serving the poor (including property title requirements and service boundaries that exclude poor neighborhoods). · Design financial incentives consistent with service expansion or improved objectives for low-income areas. Contracts are subject to negotiation, so expansion or connection mandates alone do not guarantee that concessionaires will serve poor areas. Provisions and standards that reduce service options (for example, requirements that eliminate all alternatives to in-house connections) or restrict the emergence of new service providers (for example, granting exclusivity in the service area) could do more harm than good. In two years of operation, Aguas del Illimani met its first expansion mandate and took many steps to facilitate the expansion of in-house water connections in low-income areas.